THE IMAGE OF THE WAY IN THE POETRY BOOK ‘POEMS FROM THE LOOPHOLE’ BY MAKSYM KRYVTSOV - Derkachova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article presents a comprehensive study of the poetic world of Maksym ‘Dali’ Kryvtsov – a soldier-poet and representative of the New Executed Renaissance who was killed in the war in January 2024. Based on his poetry book Poems from the Loophole, the research analyzes the image of the road and the lyrical hero’s path, as well as the functioning of the traveller figure, which emerge as key concepts shaping both the structure and semantic depth of Kryvtsov’s lyrical narrative. The purpose of the study is to identify the specific features of the poetic modelling of the road and the traveller figure in Kryvtsov’s poems. The methodology combines structural-semantic analysis of poetic texts, elements of hermeneutics, and intertextual analysis. This approach makes it possible to reveal the compositional features of the author’s poetics, uncover deeper semantic layers of war poetry, and trace the transformation of the monomyth in the context of contemporary warfare. The results of the study show that the images of the road and the traveller acquire multidimensionality. The lyrical hero becomes a warrior, a witness, and a wanderer moving between two worlds – the living and the dead, the sacred and the profane. War is interpreted as a road that performs the functions of departure, initiation, and the (im)possibility of return, while Christian images – God, Mary, the saints – acquire new symbolic roles embedded in the everyday reality of trench life. Kryvtsov’s poetry is marked by the remythologization of sacred motifs, giving the war experience a metaphysical dimension, and by the fragmentary, discontinuous structure of his poems, which reflects the psychological nature of wartime existence. The scientific novelty of the study lies in the fact that it provides the first comprehensive literary analysis of the road as a central conceptual element in the poetic world of Maksym “Dali” Kryvtsov and defines its key role in shaping the modern image of the traveller in Ukrainian war poetry. The practical significance of the research lies in its applicability to the study of contemporary Ukrainian war literature, the teaching of literary studies, and the formation of a corpus of texts representing the New Executed Renaissance. The article also contributes to a broader understanding of the role of the soldier-poet in the contemporary Ukrainian cultural space.